Testing and Simulation of Motor Insulation System under Some Artificial Environmental Conditions - I Made Yulistya Negara; Dimas Anton Asfani; Siti Sudatul Aisyah N (IAES Indonesia Section, 2014)
This study deals with the effect of humidity and contamination of salt on insulation resistance and polarization index. It investigated experimentally and is also analyzed by using its equivalent circuit. Surface leakage and absorption currents were measured to interpret the quality of insulation winding of a motor. The result shows that in all conditions, the value of absorption current is constant during the testing, meanwhile due to effect of humidity and contamination the leakage current is much larger than normal conditioned motor. Data obtained from insulation resistance test are used to calculate the resistance to ground (RTG) and capacitance to ground (CTG). RTG and CTG are then used as value of components on equivalent circuit for simulation matter. The simulation result using equivalent circuit is reasonable agree with the experiment done.